2015
DOI: 10.1007/s10439-015-1290-y
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Stage Detection Using Tracheal Breathing Sounds: A Pilot Study

Abstract: Sleep stage detection is needed in many sleep studies and clinical assessments. Generally, sleep stages are identified using spectral analysis of electrocephologram (EEG) and electrooculogram (EOG) signals. This study, for the first time, has investigated the feasibility of detecting sleep stages using tracheal breathing sounds, and whether the change of breathing sounds due to sleeping stage differs at different periods of sleeping time; the motivation was seeking an alternative technique for sleep stage iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Therefore, in this study, the Hurst component was calculated from the autocorrelation of sound energy. In-line with the findings in Soltanzadeh and Moussavi, 7 the Hurst exponent was higher during sleep indicating a more regular pattern of breathing compared to wakefulness. However, unlike the finding in Soltanzadeh and Moussavi, 7 no significant difference was found between REM and NREM of full-night data.…”
Section: Dovepresssupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, in this study, the Hurst component was calculated from the autocorrelation of sound energy. In-line with the findings in Soltanzadeh and Moussavi, 7 the Hurst exponent was higher during sleep indicating a more regular pattern of breathing compared to wakefulness. However, unlike the finding in Soltanzadeh and Moussavi, 7 no significant difference was found between REM and NREM of full-night data.…”
Section: Dovepresssupporting
confidence: 88%
“…In previous studies, sleep stages were detected overnight by Dafna et al 5,6 using an ambient microphone and in a few short segments of sleep using tracheal sound by Soltanzadeh and Moussavi. 7 In this study, significant changes were found between REM and other states only in sound features. More in-depth analysis to differentiate various sleep stages should be addressed in future studies.…”
Section: Dovepressmentioning
confidence: 50%
See 1 more Smart Citation
“…However, both PSG and H-PSG tend to involve bulky equipment that requires significant time to put on properly and to interpret; the systems tend to be cumbersome, and might themselves interact with the sleep behavior, which make them impractical for long-term sleep/wake detection. More recent methods involve less cumbersome equipment such as using a smartphone placed on the bed to track movement via accelerometers [14], using contact [15] and non-contact microphones [16], short-range doppler radar [17] and WiFi [18].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these methods use heart rate variability (HRV) [3 -5] or electrocardiogram (ECG)-derived respiration in addition to the HRV features [6] from an ECG. Other studies used peripheral arterial tone (PAT) [7], an EOG [8], tracheal breathing sound [9], or respiratory signals [10] to detect the sleep stages. Although the sleep stages could be detected using these methods (with average accuracies ranging from 56.0 % to 81.7 %), attachment of the sensor to measure the physiological signal during sleep still causes a great deal of inconvenience to the sleeper.…”
Section: Introductionmentioning
confidence: 99%